Evaluasi Kebijakan Responsif Gender Dalam Penyediaan Gerbong Khusus Wanita Pada Commuter Line JABODETABEK Tahun 2024 - 2025: Indonesia - Hauralya Salsabilla; Dede Sri Kartini; Antik Bintari (Jurnal Kebijakan Pemerintahan, 2025)
This study evaluates the gender-responsive policy of women-only carriages on the Jabodetabek Commuter Line (2024–2025). Originally introduced as affirmative action to protect women from sexual harassment, the policy also supports Indonesia’s gender mainstreaming agenda. Using a qualitative case study, data were gathered through interviews, observations, documentation, and digital ethnography, analyzed via triangulation and Miles & Huberman’s interactive model. Evaluation followed William N. Dunn’s six types: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Findings show that while the policy increases women’s sense of safety and comfort, effectiveness remains limited due to recurring harassment cases, constrained carriage capacity, and gender-insensitive evaluation tools. Efficiency is also suboptimal as the benefits do not align with the resources used. Equity and responsiveness are hindered by patriarchal norms, limited fleets, and weak victim-centered reporting systems. Overall, the policy is a relevant but partial affirmative measure, symbolic rather than structural. Strengthening requires holistic integration through fleet expansion, victim-centered SOP improvements, stricter enforcement of the Sexual Violence Crime Law (UU TPKS), and enhanced public education and gender-awareness initiatives to realize safer, more inclusive transportation. Keywords: Public Policy, Dunn’s evaluation Theory, Gender-Responsive Policy, Jabodetabek Commuter, Women-Only Carriage.